GP132 Developing research capacity: baseline survey identifying research activity, skills and supports for nurses in children's hospitals in ireland. (June 2019) - O'Keeffe, Norma; Cullinane, Anne Marie; Greensmith, Louise; Bracken, Shirley; O'Shaughnessy, Norma; Dennehy, Caitriona; Smith, Hazel; Lambert, Veronica
Abstract : Background: Children's healthcare in Ireland is currently undergoing radical transformation with the build of a new National Children's Hospital to integrate services delivered by three existing children's hospitals. The new Model of Care for Irish Paediatrics endorses research-led enquiry and translation as critical to providing excellence in clinical practice. This brings its challenges with a recognised critical deficit in the number of individuals with the skills, ambition and time to lead major research projects. The aim of this study was to identify baseline data on research activity, skills and supports for nurses in children's hospitals. Methods: A cross-sectional survey was conducted in 2018 across three children's hospitals in Ireland using a clinical nursing research questionnaire developed through adaptation of two previous established questionnaires investigating research activities, skills/abilities and supports among health care providers. All registered nurses employed in the three paediatric hospital study sites were eligible to participate. Data were analysed using descriptive statistics and thematic analysis. Results: In total 355 respondents completed the survey (overall response rate 25.1%). Statistical analysis of survey data revealed that n=100 respondents (28.2%) had been involved in a research study but only n=24 (6.8%) had been a lead investigator. Twenty-one (5.9%) respondents had a publication within the last five years and n=85 (23.9%) had presented a poster at a local (n=61, 17.2%), national (n=34, 9.6%) or international (n=22, 6.2%) conference. Just over a fifth (n=74; 20.8%) had given an oral presentation at a local (n=59, 16.6%), national (n=26, 7.3%) or international (n=15, 4.2%) conference. On a whole, respondents self-rated their research skills as weak or average across all stages of research (with overall research competence rated as weak/average n=236, 66.5%). Thematic analysis of qualitative data revealed six themes including; time for research; incentives to engage in research; awareness and promotion of research; research training needs; supports required to enable research; and perceived challenges impacting on nurses' ability to undertake research. Conclusions: There is the need for a clearer strategic vision and political commitment to establish a research supportive environment for nurses working in children's hospitals to conduct research. Particular recommendations focus on additional time, mentorship, communication, information and education. This survey is one aspect of a number of activities informing the development of a research capacity building strategy for children's nursing at a time of reconfiguration of paediatric health services in Ireland.